xuan de mysterious virtue: Wu wei and the non-paradoxical politics of the Dao - Goodfield, Eric Lee (Asian philosophy, 2024)
In his work on Wu wei, Edward Slingerland argues that the classical Chinese ideal is an inherently paradoxical concept that is first and foremost spiritual and political only secondarily. Through a close reading of the Dao de Jing, the first major classical text to substantially deploy and develop the concept, I argue that Wu wei isn’t inherently paradoxical and that this is seen precisely when it is viewed in terms of its political primacy. On my reading, the emergence of Wu wei in the Daoist canon is an equilibrating moment of political mediation between the highly intentionalized sphere of human pursuits and the purposeless fluidity and boundless flux of the natural world. Wu wei here takes on a different aspect—mystery rather than paradox—when considered within a form of political collectivity in which the intentional and the innate, purposive and natural are constantly juxtaposed and contending with one another.